Santalum Genus: phytochemical constituents, biological activities and health promoting-effects - Sharifi-Rad, Javad; Quispe, Cristina; Turgumbayeva, Aknur; Mertdinç, Zehra; Tütüncü, Sena; Aydar, Elif Feyza; Özçelik, Beraat; Anna, Stępień-Warda; Mariola, Staniak; Koziróg, Anna; Otlewska, Anna; Antolak, Hubert; et al. (Zeitschrift für Naturforschung C. A journal of biosciences, 2023)
genus belongs to the family of Santalaceae, widespread in India, Australia, Hawaii, Sri Lanka, and Indonesia, and valued as traditional medicine, rituals and modern bioactivities. Sandalwood is reported to possess a plethora of bioactive compounds such as essential oil and its components (α-santalol and β-santalol), phenolic compounds and fatty acids. These bioactives play important role in contributing towards biological activities and health-promoting effects in humans. Pre-clinical and clinical studies have shown the role of sandalwood extract as antioxidant, anti-inflammatory, antibacterial, antifungal, antiviral, neuroleptic, antihyperglycemic, antihyperlipidemic, and anticancer activities. Safety studies on sandalwood essential oil (EO) and its extracts have proven them as a safe ingredient to be utilized in health promotion. Phytoconstituents, bioactivities and traditional uses established sandalwood as one of the innovative materials for application in the pharma, food, and biomedical industry.